Early detection of peritonitis in continuous ambulatory peritoneal dialysis patients by cytokine measurements - (:unkn) unknown (WALTER DE GRUYTER & CO, 2003)
Continuous ambulatory peritoneal dialysis (CAPD) carries a risk of peritonitis which is accompanied by mild symptomatology. Culture of effluent has yielded organism in 50% of cases. Peritoneal phagocytes produce tumor necrosis factor-a and interleukin (IL)-1 in response to contact with bacteria, initiating an inflammatory cascade which leads to IL-6 and IL-8 secretion. Additonally, neutrophils undergo an increase in oxidative metabolism. We have evaluated the diagnostic accuracy of effluent measurements of TNF-alpha, IL-6, IL-8, and oxidative metabolism markers in these patients. Dialysate fluids (n = 65) were collected from non-infected patients and those presenting with acute peritonitis. Positive culture proved the diagnosis. Oxidative markers and nitric oxide were measured by chemiluminescence. Cytokines were measured by solid phase chemiluminescent immunometric assay (Immulite, DPC, USA). Receiver operating characteristic (ROC) curves were used to assess the diagnostic accuracy and the areas under curves were calculated for comparison. All effluent cytokines and oxidative markers were significantly higher in patients with peritonitis when compared to those without (p < 0.05). Significant correlations were evident between IL-6 and IL-8, lucigenin chemiluminescence and luminol chemiluminescence, lucigenin chemiluminescence and IL-6 or IL-8, and luminol chemiluminescence and IL-6 or IL-8. ROC curves showed that the ability of IL-6, IL-8, lucigenin chemiluminescence, and luminol chemiluminescence to differentiate CAPD patients with peritonitis from non-infected cases exceeds that of polymorphonuclear leukocyte count.
Keywords: continuous ambulatory peritoneal dialysis; CAPD; peritonitis; chemiluminescence; IL-6; IL-8; tumor necrosis factor-alpha; TNF-alpha; MESOTHELIAL CELLS; NITRIC-OXIDE; UREMIC PATIENTS; TNF-ALPHA; CAPD; INTERLEUKIN-8; EFFLUENT; EXPRESSION; IL-1-BETA